x(9-4)+2=-98

Simple and best practice solution for x(9-4)+2=-98 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(9-4)+2=-98 equation:


Simplifying
x(9 + -4) + 2 = -98

Combine like terms: 9 + -4 = 5
x(5) + 2 = -98

Reorder the terms for easier multiplication:
5x + 2 = -98

Reorder the terms:
2 + 5x = -98

Solving
2 + 5x = -98

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 5x = -98 + -2

Combine like terms: 2 + -2 = 0
0 + 5x = -98 + -2
5x = -98 + -2

Combine like terms: -98 + -2 = -100
5x = -100

Divide each side by '5'.
x = -20

Simplifying
x = -20

See similar equations:

| 2x-3(x+8)=21 | | (x+2)(x)(5)=240 | | -4a+a=30 | | x-8.9=-4.4 | | -77-7x=48-2x | | -16c-0.52=-2.11-16c | | -0.6+(-42)=-1.4 | | 2x-9+6x=9-15 | | 4x+13=3+6x-6 | | -4r=5.8r-9.8r | | (2i)(6-8i)= | | 2x(y-3)+7x=14 | | -4-8=4x+3-3x | | -.75(2X+1)=3(x+4)+4 | | 3x+1+15=2x+4(x+1) | | 0.2w-2.46=0.4w | | z+39=17 | | 3x-12+6x+12=8x+17 | | .67h-.33h+11=8 | | 3=-x-5 | | -15+2m=2m | | 5(4x-3)+9=-5 | | 2/3+3m/5=-31/5 | | -9.9h+10.52=-8.28-9.9h+18.8 | | 2x+3(4-5+5)=6-6+7 | | ln(9x+10)-ln(x)=ln(10) | | 14-(9t-2)=-t+30 | | -3(-c-18)=-3-18 | | (5x+10)+58=(11x+2) | | 9x^2-25x+16=0 | | 8x^2-28X+24=0 | | .5t-3t+5=0 |

Equations solver categories